Analisis Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Di Atlantis Gold PTC Mall Palembang - Marsella, Marsella; Artina, Nyimas (LPPM Universitas Multi Data Palembang, 2024)
The aim of this research is to find out how product quality and price impact consumer decisions to buygoods at Atlantis Gold PTC Mall partially and simultaneously. The sample in the research was 200 respondents. The data collection method uses a questionnaire with a sampling technique carried out using non-profitability sampling with a purposive sampling method. The research results for the partial test, the t-count value for the price variable is 11.123 with a significance of 0.000, the t-count value for the product quality variable is 7.374 with a significance of 0.000. For the simultaneous test, the Fcount value is 132.603 with a significance of 0.000 < 0.05. The results of this research are that price and product quality have a positive and significant influence on purchasing decisions at the Atlantis Gold PTC Mall Palembang shop, both partially and simultaneously.